Carbon copy: The mock bureaucratic setting of colliery explosions in early twentieth century Britain and at Pike River, New Zealand. Issue 1 (8th January 2018) - Reveley, James; Singleton, John
Abstract : Purpose: By juxtaposing fatal colliery explosions in early twentieth-century Britain and in 2010 at Pike River, New Zealand, this paper aims to investigate the generalizability of the mock bureaucracy concept to underground coal mining disasters. Design/methodology/approach: The main source is published official accident inquiries; a methodological reflection justifies the use of these materials. Findings: Mock bureaucracies existed in the British underground coal mining milieu from the time when safety rules were first formulated in that industry context. As for Pike River, it is an exemplary case. The development in 1970s Britain of a new approach to safety management (the Robens system), and its subsequent export to New Zealand, means that a contemporary coal mine under financial duress, such as Pike River, is a prime site for mock bureaucracy to flourish. Originality/value: Although the concept of mock bureaucracy has been applied to an explosion in an underground coal mine before, this is the first paper to explore the concept's historical usage and generalizability in explaining the environing context of such explosions.